Cochrane Database of Systematic Reviews 2011
DOI: 10.1002/14651858.cd008716.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics for patients with hepatic encephalopathy

Abstract: Trusted evidence. Informed decisions. Better health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 184 publications
4
60
0
1
Order By: Relevance
“…Lactulose is used to acidify feces and sequester ammonia as ammonium, but lactulose is poorly tolerated, resulting in poor adherence (13). In a mouse model of thioacetamide-induced liver injury, a lactobacillus probiotic has been reported to reduce ammonia levels and mortality (14), but these benefits have not been extended to human studies (15,16). While promising, studies of probiotic therapies in humans described to date have suffered from methodological limitations, did not document long-term effects, and showed consistently minimal effects on outcome, motivating efforts to engineer more resilient and effective bacterial communities.…”
Section: Introductionmentioning
confidence: 99%
“…Lactulose is used to acidify feces and sequester ammonia as ammonium, but lactulose is poorly tolerated, resulting in poor adherence (13). In a mouse model of thioacetamide-induced liver injury, a lactobacillus probiotic has been reported to reduce ammonia levels and mortality (14), but these benefits have not been extended to human studies (15,16). While promising, studies of probiotic therapies in humans described to date have suffered from methodological limitations, did not document long-term effects, and showed consistently minimal effects on outcome, motivating efforts to engineer more resilient and effective bacterial communities.…”
Section: Introductionmentioning
confidence: 99%
“…Вместе с тем отмечено существенное снижение концентрации аммиака. Авторы пришли к заключе-нию о необходимости проведения дальнейших ран-домизированных клинических исследований [17].…”
Section: результаты исследования и обсуждениеunclassified
“…Loguercio et al 36,37 showed that long-term administration of Enterococcus faecium (SF68) is at least as useful as lactulose for the chronic treatment of chronic HE. In a meta-analysis by McGee et al 38 …”
Section: Probioticsmentioning
confidence: 99%